The institutional status of the Methodist learning centers in the Mindanao Philippines annual conference - Hermano, Rosemarie Claro (2001)
This study sought to describe and analyze the status of 19 Methodist preschools in Mindanao Philippines Annual Conference (diocese). The focus was on curriculum, physical environment, staff qualifications, and financial conditions. There were nine administrative pastors and 22 teachers as respondents. The researcher developed questionnaire, interview schedule and observation checklist as tools in gathering data. Frequency distribution, percentage, means, and t-test for independent samples were used in the analysis. Findings revealed that there were no significant differences between the perceptions of teachers and pastors on the status of the curriculum and physical environment. Curriculum content was perceived to be high status. School sites, classroom furniture and health facilities were of high status. However, playground apparatus and instructional materials were of low status/Academic qualifications of administrators were also of low status. Teachers specialized in Bachelor in Kindergarten Education and therefore where of high status. However, the schools had a low financial status. Most sponsoring churches gave subsidy to the preschools. Compensation given to teachers was very minimal. This study recommended that: a.) salary of teachers should be raised; b.) school administrators should be provided; d.) government should extend assistance to Church-based schools; e.) Methodist preschools should be encouraged to comply with DECS requirements, f.) DECS should review and update Order 107; g.) Institutions that offer early childhood education courses should advocate for preschool programs; and h.) research be conducted with more respondents and qualitative methods.